Successful Obliteration of a Pseudoaneurysm from Post-CEA Repair Secondary to a Pruitt-Inahara Shunt Using a Stent Graft - Vishal Dahya; Prasad Chalasani (Case Reports in Vascular Medicine)
Pseudoaneurysms of the carotid artery are very uncommon complications following carotid endarterectomy. Pseudoaneurysms are usually caused by any kind of blunt injury or trauma during carotid artery surgery. CEA has become an increasingly more common vascular surgery performed in the United States. The standard of treatment for a carotid PA has been open surgical repair with excision of the defect and then a graft reconstruction of the artery. Advancements in endovascular intervention have helped to make it a more popular choice in treatment because of the positive results and less invasive approach. This case report describes the successful obliteration of a large post-CEA PA using a stent graft. The PA was likely secondary to the use of a Pruitt-lnahara Shunt because it was found to be distal to the endarterectomized area of the carotid artery which means that the defect was likely caused by the balloon portion of the shunt. This case demonstrates the feasibility of using endovascular interventional techniques to treat a PA using a stent graft.